ABILITY OF INFRASTRUCTURE DEVELOPMENT IN EXPLAINING ECONOMIC GROWTH OF WEST KALIMANTAN PROVINCE IN 2010 – 2014 PERIOD - B1011131115, ASYUR RAHMAN (Jurnal Pembangunan dan Pemerataan, 2017)
Increased economic growth is done by one of the infrastructure development. Infrastructure development is needed to support the community in developing products and services in their respective regions. However, the development of infrastructure facilities and infrastructure such as long road infrastructure, electricity infrastructure, clean water infrastructure and inadequate Puskesmas infrastructur not all completed infrastructure in it’s development process in West Kalimantan Province become a challenge for local government because infrastructure itself is a capital in reaching the entry investments, promote economic growth, open isolation among regions, increase activities, increase access to technology and increase community mobility and social contact among residents in various regions. The purpose of this research is to see the influence of long road infrastructure development, electricity, clean water and puskesmas to economic growth in West Kalimantan Province in 2010 - 2014. Data analysis technique used is multiple regression with Fixed effect method. Data sources obtained are Central Bureau of Statistics, BAPPENAS and Ministry of energy and mineral resource. The result of this research is the influence of negative and significant negative road infrastructure development, the influence of negative and insignificant electricity infrastructure development, the influence of positive and significant clean water infrastructure development and the positive and insignificant impact of infrastructure development of puskesmas. Keywords: Economic Growth, Road Infrastructure Development, Electricity Infrastructure, Clean Water Infrastructure, Puskesmas Infrastructure.